SPRTN metalloprotease participates in repair of ROS-mediated DNA-protein crosslinks - Luke Erber; Arnold S. Groehler; Cesar I. Cyuzuzo; Jahan Baker-Wainwright; Reeja S. Maskey; Lei Li; Yuichi J. Machida; Natalia Tretyakova (Scientific Reports)
Abstract Exposure to reactive oxygen species (ROS) can induce DNA-protein crosslinks (DPCs), unusually bulky DNA lesions that block replication and transcription and play a role in aging, cancer, cardiovascular disease, and neurodegenerative disorders. Repair of DPCs depends on the coordinated efforts of proteases and DNA repair enzymes to cleave the protein component of the lesion to smaller DNA-peptide crosslinks which can be processed by tyrosyl-DNA phosphodiesterases 1 and 2, nucleotide excision and homologous recombination repair pathways. DNA-dependent metalloprotease SPRTN plays a role in DPC repair, and SPRTN-deficient mice exhibit an accelerated aging phenotype and develop liver cancer early in life. We investigated the role of the SPRTN enzyme in the repair of DPCs produced by a free radical mechanism. Sprtn-deficient MEF cells treated with ionizing radiation had higher levels of total DPCs and exhibited greater sensitivity upon exposure to hydrogen peroxide and other crosslinking agents including cisplatin, phosphoramide mustard, and 1,2,3,4-diepoxybutane. Using a sensitive and accurate nanoLC-ESI+-MS/MS assay, we specifically measured the radical-induced crosslinking of thymidine in DNA crosslinking of thymidine in DNA to tyrosine in proteins (dT-Tyr) in the tissues of SPRTN hypomorphic (SprtnH/H) and wild type mice. Genomic DNA isolated from the tissues of SPRTN hypomorphic (SprtnH/H) mice exhibited higher levels of dT-Tyr in the liver, brain, heart, and kidney than wild-type animals. Overall, our results are consistent with the understanding that SPRTN has a role in maintaining genomic integrity upon exposure to ionizing radiation and endogenous reactive oxygen species.